Family Background or the Characteristics of Children: What Determines High School Success in Germany? - Benjamin Balsmeier; Heiko Peters (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
It is becoming more and more important to be highly skilled in order to integrate successfully into the labor market. Highly skilled workers receive higher wages and face a lower risk of becoming unemployed, compared to poorly qualified workers. We analyze the determinants of successful high school graduation in Germany. As our main database, we use the youth file of GSOEP for the period extending from 2000 to 2007. Because the decision as to which secondary school track to attend - general school (Hauptschule), intermediate school (Realschule) or high school (Gymnasium) - is made after the end of elementary school (Grundschule) at age of ten, parents are responsible for this decision. Therefore, the characteristics of the child as well as those of its parents are the main determinants of educational attainment. We also include the characteristics of grandparents in our regression framework, something which has not been done in any previous study so far. In order to disentangle the determinants of successful graduation at high school, we use the Cox proportional hazard model. We find markedly different determinants of successful graduation for males and females. Furthermore, the results indicate a strong linkage between mothers and daughters, as well as between fathers and sons.
Keywords: A21; C41; I21; 330; high school graduation; Cox proportional hazard model; Germany